ANALYSIS OF THE WILLINGNESS TO PAY FOR THE CONSUMPTION OF GANYONG AS A LOCAL FOOD IN GUNUNGKIDUL REGENCY - Yudya Alif Ridhoni Prakusya; Sri Setiawati Tumuyu; Tri Edhi Budhi Soesilo (ITB AAS Indonesia Surakarta, 2026)
The food system’s reliance on homogeneous commodities and imported products has created vulnerabilities in food security. Local foods, which are considered to have economic potential and could serve as a solution to this problem, have not yet been adequately developed. This study aims to analyze consumers’ willingness to pay for ganyong as a local food in Gunungkidul Regency and to evaluate its economic potential if developed optimally. The method used was a statistical analysis of 107 respondents who directly provided their willingness-to-pay values for ganyong as a local food. The results show that the WTP for ganyong in Gunungkidul Regency is Rp10,000/kg. In terms of preferences, taste and nutritional value were found to have a significant influence on WTP, while sociodemographic characteristics such as age, gender, education, and expenditure level did not show a significant direct influence. These findings can serve as a reference for unlocking the significant economic potential of developing ganyong as a local food crop in Gunungkidul Regency. This study concludes that ganyong, as a local food crop, has a high willingness-to-pay value, strong competitiveness, and great potential to support food security while boosting local economic growth in Gunungkidul Regency